Fenomologi Pengalaman Komunikasi Mahasiswa Etnik Gayo Di Universitas Medan Area - Angga Pradana Aulia Hutagalung; Nadra Ideyani Vita (Journal of Education, Humaniora and Social Sciences (JEHSS), 2025)
This study aims to understand the communication experiences of Gayo students at Universitas Medan Area (UMA) and the adaptation strategies they use to overcome intercultural communication barriers. Based on interviews with Gayo students currently studying at UMA, the research findings indicate that Gayo students experience culture shock due to differences in communication styles, language, and social values compared to local students. In response to these barriers, they developed various adaptation strategies, such as using formal Indonesian, avoiding conflicts, and seeking peers from Gayo for support. The findings also show that despite initial difficulties in interacting, Gayo students gradually adapt and create new meanings in their communication process, grounded in their personal experiences and cultural perspective shifts.